2013
DOI: 10.1161/strokeaha.111.000126
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Thrombolysis in Stroke Mimics

Abstract: The proportion of stroke mimics varies between 1% and 16% in hospital-based IVT registers. [6][7][8][9][10][11][12][13][14][15] Knowledge of safety of IVT in stroke mimics is important because treatment in these patients can only be accepted as long as the complication rate is very low. Serious complications of IVT in stroke mimics have not been reported so far, but most studies were from single centers and were based on a relatively small number of Background and Purpose-Intravenous thrombolysis for acute isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(101 citation statements)
references
References 29 publications
3
93
2
2
Order By: Relevance
“…[16][17][18][19] Local study investigators completed the forms using prospectively ascertained in-hospital IVT registries. Completed forms from all centers were compiled in the coordinating center in Amsterdam, where data were pooled and analyzed as described previously.…”
Section: Methods Study Population Procedures and Outcomesmentioning
confidence: 99%
“…[16][17][18][19] Local study investigators completed the forms using prospectively ascertained in-hospital IVT registries. Completed forms from all centers were compiled in the coordinating center in Amsterdam, where data were pooled and analyzed as described previously.…”
Section: Methods Study Population Procedures and Outcomesmentioning
confidence: 99%
“…However, we found no sex differences between SMs and confirmed strokes, and our patients with SMs did not have decreased stroke severity compared to those with confirmed strokes; this differs from prior work. 4,5 Regarding SM predictors, other studies have found lower rates of atrial fibrillation and hypertension in SMs compared with confirmed strokes. Without a detailed medical history, we cannot fully compare how our patients with SMs differed medically from patients with confirmed strokes.…”
Section: Discussionmentioning
confidence: 97%
“…A proportion of patients who present with stroke symptoms and are treated with IV tPA are later found to have a diagnosis other than AIS upon further workup. 4 These patients are considered to have stroke mimics (SMs). Although SM treatment is considered safe with low rates of intracerebral hemorrhage, the complication rate is not zero.…”
mentioning
confidence: 99%
“…Zinkstok et al 11. reported that epileptic seizures (41%) and psychiatric disorders (28%) are the most common diseases that can cause stroke mimics, and the frequency of hypoglycemia is low (1%).…”
Section: Discussionmentioning
confidence: 99%